PENGARUH PENGGUNAAN HEEL PAD TERHADAP DERAJAT NYERI PADA PENGGUNA HIGH HEELS - Sysbania Sysbania; Yopi Harwinanda Ardesa; Muhammad Syaifudin (Jurnal Keterapian Fisik, 2018)
Abstract Background : Along with the development of technology, increasing the industrial era in Indonesia cause a large number of companies, factories and malls are appeared to support the movement of the economy. Sales Promotion Girl (SPG) is one of the jobs that appear due to the proliferation of mall in a major city. The workers of this profession are typically women who have interesting physical character as an attempt to attract the attention of consumers. One of the performance standard is set by the company is wearing high heels and looking interesting. Methods : this study was carried out in 17 May – 1 June 2017 in PT. Matahari Department Store Solo Square by using quasi eksperimental methods with one group pre test and post test design. The number of samples are 20. Results : the results of this research are descriptive from 20 samples have already weared heel pad there is 80% of light pain scale and 20% of moderate pain scale, where before wearing heel pad there is 10% of light pain scale, 75% of moderate pain scale and 15% of severe pain scale. The research is the analysis based on the results of the analysis of the data obtained that value of wilcoxon test is 0,000 where the P < 0,05. Conclusion : from the results of the research is there is the influence of the wear of the heel pad against the pain degree of the high heels wearers.